‘Bear with My Word of Comfort’: Consolatory Strategies in the Letter to the Hebrews - Pracht, Erich Benjamin (Journal for the study of the New Testament, 2025)
In this study, I argue that the book of Hebrews contains five consolatory strategies that recur in the letters of Cicero, Seneca, and Plutarch. I relate Hebrews to the Greco-Roman consolatory tradition in terms of general modes of socio-literary practice that cut across traditional dividing lines such as ethnicity, language, and philosophical outlook. In this way, I show how Greco-Roman consolation, which is typically overlooked in scholarship on Hebrews, sheds informative light on the author’s literary strategies and aims. I situate Hebrews against the background of hostilities faced by the original audience and the destruction of the temple, both of which caused distress and disorientation and thereby created the need for consolation. I argue that, given the historical circumstances that provided the occasion for writing and the consolatory strategies the author deploys, consolation is among the author’s primary literary objectives. As a result, I find that the author’s designation of his work in Heb. 13.22 is best translated as a ‘word of comfort’.